Detecting low-mass haloes with strong gravitational lensing: II. Constraints on the density profiles of two detected subhaloes - Despali, Giulia; Heinze, Felix M.; Fassnacht, Christopher D.; Vegetti, Simona; Spingola, Cristiana; Klessen, Ralf S.; Tajalli, Maryam (Astronomy and astrophysics, 2025)
Aims: Strong gravitational lensing can detect the presence of low-mass haloes and subhaloes through their effect on the surface brightness of lensed arcs. We carry out an extended analysis of the density profiles and mass distributions of two detected subhaloes, with the intention of determining whether their properties are consistent with the predictions of the cold dark matter (CDM) model. Methods: We analysed two gravitational lensing systems in which the presence of a low-mass subhalo has previously been reported: SDSSJ0946+1006 and JVASB1938+66. We modelled these detections by assuming four different models for their density profiles and compared our results with predictions from the TNG50 simulation. Results: We find that the detected subhaloes are well modelled by steep inner density slopes, close to or steeper than isothermal. The Navarro-Frenk-White (NFW) profile thus needs extremely high concentrations to reproduce the observed properties, which are outliers of the CDM predictions. We also find a characteristic radius within which the best-fitting density profiles predict the same enclosed mass. We conclude that the lens modelling can constrain this quantity more robustly than the inner slope. We find that the diversity of subhalo profiles in TNG50, consistent with tidally stripping and baryonic effects, is able to match the observed steep inner slopes, somewhat alleviating the tension reported by previous works even if the detections are not well fitted by the typical subhalo. However, while we find simulated analogues of the detection in B1938+666, the stellar content required by simulations to explain the central density of the detection in J0946+1006 is in tension with the upper limit in luminosity estimated from the observations. New detections will increase our statistical sample and help us reveal more about the density profiles of these objects and the dark matter content of the Universe.